La influencia de Rodin en la obra de Rilke - Pastor Hurtado, Óscar (Dicenda. Estudios de lengua y literatura españolas, 2008)
In summer 1902 the poet Rainer Maria Rilke goes to Paris in order to meet the renowned sculptor Auguste Rodin and write about him a monographic work for Breslau University. Actually, this is only the pretext that allows to Rilke to get closer as an artist to the great french creator and learn from him as much as possible. Far from the romantic concept of inspiration, Rodin establishes the constancy in the observation of things, since beauty is in everything. Under his influence Rilke starts the «poemthings » stage and write two books impregnated of great deal of plasticity: «New poems» (1907) and «The other part of the new poems» (1908). In spite of their supposed objectivity these books have however a symbolist character, since according to Rilke reality becomes firm through the poet’s voice and vision.